VD_FINDINFO HC / 2014 / 58 vom 21. Januar 2014 - VD Tribunal cantonal (2014)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, IMPÔT, MINIMUM VITAL, MODIFICATION DES CIRCONSTANCES | 176 al. 1 ch. 1 CC, 179 CC